Arabic Language Learning Methodology from The Liang Gie's Perspective: Management Aspects in Education - Hasanah, Uswatun; Saleha, Ela; Maksum, M. Syukron; Irawan, Gusli Bambang (Journal of Educational Management Research, 2025)
This study examines Arabic Language Learning Methodology from Liang Gie's perspective, emphasizing its significance and relevance in the context of educational management. Using a qualitative case study design, data were collected through structured interviews with Arabic language lecturers and teachers, along with document analysis. The study reveals that the Arabic methodology course is essential for providing a solid pedagogical foundation, enabling future teachers to develop systematic, contextually relevant, and practical learning plans. It bridges the complexities of Arabic, such as grammar and pronunciation, with the students' learning processes. The course's urgency is evident in its focus on fostering the linguistic, intellectual, and professional competencies educators need to meet the demands of Islamic education and contemporary pedagogical trends. The research also underscores the importance of this methodology in addressing challenges such as multiculturalism, digital learning, global competencies, and inclusive, project-based teaching approaches. The study concludes that Arabic Language Learning Methodology is a critical skill-building discipline, essential for developing educators who are capable of enhancing the quality of Arabic language instruction in the digital age.